Mesoporous tantalum oxide nanomaterials induced cardiovascular endothelial cell apoptosis via mitochondrial-endoplasmic reticulum stress apoptotic pathway. (31st December 2023) - Jiao, Yuanyong; Zhang, Xiwei; Yang, Hongyu; Ma, Hao; Zou, Junjie
Abstract: Along with its wide range of potential applications, human exposure to mesoporous tantalum oxide nanomaterials (PEG@mTa2 O5 ) has substantially risen. Accumulative toxic investigations have shown the PEG@mTa2 O5 intake and cardiovascular diseases (CVD). Endothelial cell death is crucial in the onset and development of atherosclerosis. Still, the molecular mechanism connecting PEG@mTa2 O5 and endothelium apoptosis remains unclear. Herein, we studied the absorption and toxic action of mesoporous tantalum oxide (mTa2 O5 ) nanomaterials with polyethylene glycol (PEG) utilizing human cardio microvascular endothelial cells (HCMECs). We also showed that PEG@mTa2 O5 promoted apoptosis in endothelial cells using flow cytometry and AO-EB staining. In conjunction with the ultrastructure modifications, PEG@mTa2 O5 prompted mitochondrial ROS production, cytosolic Ca 2+ overload, ΔΨm collapse, and ER stress verified by elevated ER-Tracker staining, upregulated XBP1 and GRP78/BiP splicing. Remarkably, the systemic toxicity and blood compatibility profile of PEG@mTa2 O5 can greatly improve successive therapeutic outcomes of NMs while reducing their adverse side effects. Overall, our findings suggested that PEG@mTa2 O5 -induced endothelium apoptosis was partially mediated by the activation of the endoplasmic reticulum stress-mitochondrial cascade.